Learning from Asian philosophy - Kupperman, Joel (Oxford University Press, 1999)
Showing how philosophical topics can benefit from interaction with Asian philosophy, this text explores: the formation of the self as an ethical problem; the fluidity of the self; the ethical nature of choice; the scope and demands of ethics.